(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Glenoid version assessment has often been crucial in shoulder procedures. There are no consensus regards the proper method of version measurement. However, the Freidman method has been the most familiar method for surgeons, various recent methods were reported to limit variational measurement errors, and to reach a uniform methodology for calibration with the least measurement bias. This study aims at reviewing different measurement strategies and pointing out the merits and limitations of each.